Discrepancy between one-stage and chromogenic factor VIII activity assay results can lead to misdiagnosis of haemophilia A phenotype - Oldenburg, J.; Pavlova, A. (Hämostaseologie, 2010)
Severity of bleeding phenotype in hemophilia A (HA) depends on the underlying mutation in the F8 gene and, ultimately, on the concentration and functional integrity of the factor VIII (FVIII) protein in circulating plasma. Initial diagnosis for HA and monitoring of treatment is typically performed by measuring of FVIII activity by either one-stage assay or chromogenic assay.We review evidence for why both types of assay do not give comparable results in a significant proportion of patients with non-severe haemophilia A and why the discrepancy in results between both methods segregates with distinct subclasses of known missense mutations causing haemophilia A. The current understanding of the mechanistic basis for how FVIII:C assay discrepancies arise are discussed.We propose that both methods should be used in initial patient diagnosis along with follow-up genetic analysis to avoid potential misdiagnosis and to optimize treatment monitoring of patients with HA phenotypes.
Keywords: Assay discrepancy; FVIII:C; haemophilia A; factor 8 gene mutations